Dimethyl N-(4-phenyl-1,3-thiazol-2-yl)-dithioimidocarbonate - Yildirim, Sema Ozturk; Akkurt, Mehmet; Koca, Murat; Sekerci, Memet; Fun, H. -K. (Int Union Crystallography, 2006)
The title compound, C12H12N2S3, was synthesized by the reaction of CS2 and CH3I with 2-amino-4-phenyl-1,3-thiazole in the presence of concentrated aqueous NaOH. The bond lengths and angles are normal. The crystal packing is stabilized by van der Waals forces.
Keywords: Diheterocyclic Compounds; Derivatives Thereof; 2-Arylamino-2-Imidazolines